2018
DOI: 10.22161/ijeab/3.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biogas from Organic Waste and its Utilization as an Alternative Energy Source

Abstract: Abstract-As a result of increase in human need

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…From this statement, it was found that the four variables had gone through the methanogenesis stage which is the last stage in the formation of biogas and had sufficient CH4 content to carry out the combustion reaction. The methanogenesis stage has the following reactions as shown in equation ( 6) and ( 7) (Sriharti et al 2018):…”
Section: Biogas Quality Analysismentioning
confidence: 99%
“…From this statement, it was found that the four variables had gone through the methanogenesis stage which is the last stage in the formation of biogas and had sufficient CH4 content to carry out the combustion reaction. The methanogenesis stage has the following reactions as shown in equation ( 6) and ( 7) (Sriharti et al 2018):…”
Section: Biogas Quality Analysismentioning
confidence: 99%
“…It assumed 1 kg of soybeans was able to produce 9.5 liters of tofu wastewater, then the potential for biogas produced about 15 liters per 1 kg soybeans. If we assumed the total energy required for cooking for 4-5 persons were 1.5 m 3 of biogas, then 100 kg of soybeans were needed to generate biogas in order to meet the needs of cooking for 1 family that consists of 4-5 persons (Sriharti et al, 2018).…”
Section: Management Strategy Of Tofu Wastewatermentioning
confidence: 99%
“…Given the increase in fuel prices due to the increase in world oil prices, the government is encouraged to deal with energy issues. One of the efforts to tighten fuel oil is to look for alternative renewable energy sources (Sriharti, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%